"FAROESTE CABOCLO" AND "THE COUNT OF MONTE CRISTO": A POSSIBLE COMPARISON - Nery Carneiro, Everton; Libertadoira Borges Carneiro, Ivana (Revista Gênero e Interdisciplinaridade, 2025)
This work compares the song "Faroeste Caboclo" by the band Legião Urbana with the film "The Count of Monte Cristo" (2024), based on the novel by Alexandre Dumas. The aim is to investigate, from an intermedial and intertextual perspective, the thematic, structural, and stylistic convergences and divergences between these two works, focusing on universal themes such as revenge, justice, and redemption. The overall objective is to analyze how different artistic languages, music and cinema, address human experiences of pain, exclusion, resistance, and transformation, and how these narrative forms critique contexts of social inequality and oppression. The methodology combines film analysis, based on the concepts of Manuela Penafria (2009), and musical semiotics, according to Cleyton Vieira Fernandes (2014), allowing for a cross-reading of the narrative, symbolic, and expressive resources of each work. The theoretical framework is anchored in authors such as Paul Ricoeur (2010), Muniz Sodré (1988), Coelho (2002), and Tzvetan Todorov to discuss narrative structures, as well as Croatto (2001), Saussure, Peirce, and Bourdieu (2010) to explore the symbolic and ideological dimensions of languages. As a result, the research shows that, despite cultural and temporal differences, the two works share archetypes and narrative strategies that enhance their social critiques. João de Santo Cristo and Edmond Dantès, each in their own context, are tragic characters driven by a justice that mixes with revenge, exposing the moral contradictions of their worlds. Both narratives destabilize boundaries between ethics and violence, reason and emotion, revealing the power of art in expressing the human condition.